Rapid Unmasking of Immune-related Adverse Events After Discontinuation of Chemotherapy in Chemo-immunotherapy Regimens. Issue 4 (10th May 2022) - Riopel, Nicholas D.; Chu, Quincy; Walker, John; Ye, Carrie
Abstract : Pembrolizumab is an immune-checkpoint inhibitor (ICI) of programmed cell death protein 1 (PD-1), which restores T–cell-mediated antitumor immune activity and therefore enhances the body's immune response to cancer cells. Due to the nature of this therapy, immune-related adverse events (irAE) can manifest in nearly every organ system. Chemo-immunotherapy regimens are now considered first-line treatment for several cancers, with recent literature suggesting there are higher rates of certain irAEs with ICI monotherapy when compared with chemo-immunotherapy combinations. In certain regimens chemo-immunotherapy induction is followed by ICI maintenance monotherapy, and data regarding irAE incidence in this transition period are very limited. We report 3 cases of patients on pembrolizumab in combination with cytotoxic chemotherapy who developed an irAE shortly following discontinuation of a chemotherapy agent. Cases were identified in the Rheumatology in Immuno-Oncology clinic at the University of Alberta and clinical data were extracted by retrospective chart review after obtaining written consent from individual patients. These findings demonstrate that chemotherapy may suppress irAEs in patients using ICIs, and that when chemotherapy agents in combined regimens are discontinued, irAEs can be "unmasked" within the following 6 weeks. Clinicians should be aware of this risk and monitor for irAE development during this critical time period. To the best of the authors' knowledge, this has not been previously reported in the literature.